How to Instant Pot : mastering all the functions of the one pot that will change the way you cook - Shumski, Daniel (Workman Publishing, 2017)
"Master the revolutionary appliance that is changing the way we cook! The only Instant Pot cookbook that is organized by function, How to Instant Pot is both a guide to understanding the Instant Pot basics and a foodie's creative collection of over 100 recipes specially crafted to take advantage of the Instant Pot's many virtues, from cooking perfect risotto in six minutes, no stirring required, to five kinds of yogurt, to creating one-hour killer chili and soups from scratch, using dried beans. Here's how to make incredible hands-off meals like Ziti and Italian Sausage, Maple-Mustard Pork Shoulder, and Korean-Style Short Ribs, plus plenty of sides, breakfasts, and desserts. In addition to a set of recipes for each function and master recipes with three variations each, there are surprising shortcuts--basics like quick pickles, perfect hard-boiled eggs, and a 30-minute "baked" potato. It's the essential purchase for every instant pot owner"--